Experiential marketing: strategies to increase the market share and strengthen energy's brand. - Azambuja, Camila Portella de; Bichueti, Roberto Schoproni (Revista de Administração da UFSM, 2016)
The competitive market has influenced the consumer behavior. Strategies to build up customer relationships and increase the visibility of brands, has become a companies' focus. We know that is not enough the brand be seen, it must be felt. Strategies before used must be adapted or changed in its entirety; therefore, the solution is to involve consumers in stocks and unforgettable experiences that provide value and brand's positive memories. In view of that the company responsible for marketing the energy drink Energy is struggling to build up their brand and be close to your target audience, in this study, we sought to understand the perception of a sample of the energy target audience, with order to identify which experience marketing strategies might include as a possible solution to remedy the deficiencies found. Grant unique experiences, entertainment and playfulness to the Energy's public, is an alternative that tends to bring the public to the brand and, gradually, increase your market share.